Dyadic Coping Across the Lifespan: A Comparison Between Younger and Middle-Aged Couples With Breast Cancer - Acquati, Chiara; Kayser, Karen (Frontiers in Psychology, 2019)
The association between dyadic coping and adjustment to cancer has been well-established. However, a significant gap in the literature is the understanding of how the life stage of couples may influence their dyadic coping and the accompanying quality of life. Although younger couples have been identified at higher risk for poor coping because of less collaborative behaviors and higher vulnerability to stress, only a limited number of studies have addressed younger women's coping with breast cancer in the context of close relationships. The present study addressed the differential impact of the illness on the quality of life and dyadic coping behaviors of younger and middle-aged dyads and the influence of relational mutuality on couples' coping in the two groups. A sample of 86 couples participated in a cross-sectional study; 35 younger couples were compared to 51 middle-aged dyads. Patients and partners completed measures of quality of life, dyadic coping, and mutuality. Independent-samples t-tests were used to examine differences in the two groups, while the Actor-Partner Interdependence Model (APIM) identified actor and partner effects of relational mutuality on dyadic coping. Younger women and their partners reported statistically significant worse quality of life and dyadic coping scores than the middle-age group. For younger couples, positive and negative coping styles were the result of both actor and partner effects of mutuality. The study highlighted the more negative impact of breast cancer on the quality of life of younger patients and partners. It also revealed a stronger influence of each partner's relational mutuality compared to the middle-age group in predicting both adaptive and maladaptive coping behavior. Future studies should continue to examine the developmental trajectory of dyadic coping across the lifespan in order to develop psychosocial interventions to promote younger dyads' coping efforts.